IMPLEMENTATION OF LOW-CODE PROGRAMMING TECHNOLOGY WITH AGILE METHOD IN DEVELOPING A PETTY CASH TRANSACTION MANAGEMENT APPLICATION (CASE STUDY: PT BANK CENTRAL ASIA TBK) - Soulani, Anin Ammbya; Nofiyati, Nofiyati; Ekowati, Nur Alfi (Jurnal Teknik Informatika (Jutif), 2024)
Conventional application development often faces challenges like extensive code writing, long development times, high costs, and difficulties in maintenance and customization. Low-code programming offers an innovative solution by minimizing manual coding and enabling application creation through visual interfaces and drag-and-drop logic. This research explains the application of low-code programming technology in developing a petty cash transaction recording application at PT Bank Central Asia Tbk, specifically in the Corporate Communication & Social Responsibility Division. The low-code approach allows for faster, more efficient, and easier-to-maintain application development. The research uses the agile method, covering plan, design, develop, test, deploy, review, and launch stages. This case study, using the OutSystems platform, shows significant benefits such as increased development time efficiency, ease of maintenance, and flexibility in meeting dynamic business needs. The developed application can be integrated into the company's existing IT environment, improving the accuracy of petty cash transaction recording and reporting, and providing easy user access. In conclusion, low-code programming technology proves to be an effective solution for developing complex business applications efficiently in terms of time and cost.